Review on the progress in emission control technologies for the abatement of CO2, SOx and NOx from fuel combustion. Issue 5 (October 2021) - Asghar, Usama; Rafiq, Sikander; Anwar, Adeel; Iqbal, Tanveer; Ahmed, Ashfaq; Jamil, Farrukh; Khurram, M. Shahzad; Akbar, Majid Majeed; Farooq, Abid; Shah, Noor S.; Park, Young-Kwon
Abstract: Extensive research has been conducted on controlling carbon dioxide (CO2 ), sulfur oxides (SOx ), and nitrogen oxides (NOx ) emissions in recent years with increasing environmental awareness. The primary contributor to climate change is the exponentially growing anthropogenic CO2, NOx, and SOx in the air from various energy and industrial sectors. Hence, several pre-combustion and post-combustion processes to mitigate these gases have been introduced and implemented. Despite the benefits of CO2, SOx, and NOx abatement technologies, researchers still have major challenges to deal with. While the removal efficiencies, operational costs, and resulting byproducts of conventional removal technologies are being improved, new technologies are also emerging. As it is evident from the current abundant reserves of coal that it will continue to be in a significant position among the principal sources of energy for more than a decade, the research for the reduction of CO2, NOx, and SOx is inevitable to save future generations from the harmful impacts of these pollutants. This review paper summarizes the progress of different emission control technologies at the plant level and introduces emerging technologies that are environment friendly. Graphical Abstract: ga1 Highlights: NOx, SOx and CO2 emissions from fuel combustion and industries are of significant concern. Several pre and post combustion processes have been devised to control emissions. Adsorption, absorption, and membrane technologies for CO2 capture have been promising. For NOx reduction, SNCR process has relatively low capital and operational cost. WFGD technology is the most extensively utilized process for SOx control.